Pengaruh Green Innovation dan Keberlangsungan Hidup Terhadap Kinerja Keuangan UMKM (Studi Kasus pada Sentra Industri Tahu Kabupaten Polewali Mandar) - Dewi, Ayu Putriana; Arif Noviarkahman Zagladi (BUDGETING : Journal of Business, Management and Accounting, 2025)
The success of the company is one of the most important points to maintain survival as well as economic and environmental resources. In this study, the problems that occur in Polewali Mandar Regency are related to the use of environmentally friendly innovations which are suspected of not being optimal or implementing GI. The purpose of this study was to determine the extent to which green innovation and survival affect the financial performance of MSMEs in the tofu industry center in Polewali Mandar Regency. This study uses quantitative methods, with the sample used by all tofu industry players from the total population of 56 tofu industry MSME players. Based on the results of this study indicate that (1) The effect of green innovation on financial performance has no visible and beneficial impact on Financial Performance, (2) Business Sustainability has a significant effect on Financial Performance.   Keywords: Financial Performance, Green Innovation, Sustainability